2020
DOI: 10.1029/2019ef001326
|View full text |Cite
|
Sign up to set email alerts
|

The Climatic Effects of Hygroscopic Growth of Sulfate Aerosols in the Stratosphere

Abstract: Solar geoengineering by deliberate injection of sulfate aerosols in the stratosphere is one of the proposed options to counter anthropogenic climate warming. In this study, we focus on the effect of a specific microphysical property of sulfate aerosols in the stratosphere: hygroscopic growth—the tendency of particles to grow by accumulating water. We show that stratospheric sulfate aerosols, for a given mass of sulfates, cause more cooling when prescribed at the lower levels of the stratosphere because of hygr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…Each of the above SAI simulations are conducted on top of the 2 × CO 2 simulation and the total amount of added aerosol mass is the same (21 Mt-SO 4 of sulphate aerosols) for all cases. This amount of aerosol addition is consistent with what is used in previous studies (Duan et al, 2018;Krishnamohan et al, 2020) and more or less offsets global mean warming caused by 2 × CO 2 . For all simulations, indirect aerosol effects (such as changes in cloud albedo and cloud lifetime) are not modeled, and the added aerosols do not get transported around or interact with other aerosol types.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Each of the above SAI simulations are conducted on top of the 2 × CO 2 simulation and the total amount of added aerosol mass is the same (21 Mt-SO 4 of sulphate aerosols) for all cases. This amount of aerosol addition is consistent with what is used in previous studies (Duan et al, 2018;Krishnamohan et al, 2020) and more or less offsets global mean warming caused by 2 × CO 2 . For all simulations, indirect aerosol effects (such as changes in cloud albedo and cloud lifetime) are not modeled, and the added aerosols do not get transported around or interact with other aerosol types.…”
Section: Methodssupporting
confidence: 90%
“…They find that stratospheric aerosols imposed at higher altitude produce more cooling as the magnitude of the effective radiative forcing is larger. On the other hand, Krishnamohan et al (2020), using small background-size sulphate aerosols, find that aerosols imposed at lower altitude produce more cooling as a result of increased scattering efficiency associated with hygroscopic growth. The contrasting conclusions between these two studies are a result of the different aerosol characteristics considered: volcanic aerosols of large size without hygroscopic growth and background aerosols of small size with hygroscopic growth.…”
mentioning
confidence: 99%
“…There are also multiple potential "design" options for deployment configuration (Kravitz et al, 2016), ranging from deployment timing, extent, placement, to aerosol selection (Pope et al, 2012;Keith et al, 2016;MacMartin et al, 2017MacMartin et al, , 2019Kravitz et al, 2019;Visioni et al, 2020a). The extent of cooling for example not only depends on how much aerosol is released, but the height of injection in atmosphere (lower stratosphere injection produces more cooling) (Bala, 2009;Krishnamohan et al, 2020). Much of the existing study on SAI assumes injection along the equator (MacMartin et al, 2017).…”
Section: Discussion: Building the Policy Boundaries For Climate Engin...mentioning
confidence: 99%
“…The latter reported that the incremental increase with altitude of AOD per unit injection is smallest at the equator and increases as injection location moves further from the equator; this is because, as mentioned above, placing aerosols into a lower‐altitude branch of the BDC causes them to be removed from the stratosphere more quickly, and this effect is stronger at higher latitudes. Finally, a lower‐altitude aerosol layer can also see increased aerosol size due to hygroscopic growth (K. Krishnamohan et al., 2020) as lower‐stratospheric heating increases water vapor transport into the lower stratosphere (see radiative feedbacks below), which could increase or decrease AOD per unit SO 2 injection depending on the resultant aerosol size. Radiative feedbacks, which affect the amount of surface cooling produced per unit of AOD. First, a sulfate aerosol layer closer to the tropopause heats the tropical tropopause layer, allowing more water vapor to transport into the stratosphere.…”
Section: Introductionmentioning
confidence: 99%